The Effect of Aquatic Plyometric Training on Jump Performance Including a Four-week Follow-up in Youth Female Volleyball Players - Ruschel C.* (2022)
© 2022 Elisa Dell'Antonio, Caroline Ruschel, Marcel Hubert, Ricardo Dantas De Lucas, Alessandro Haupenthal, Helio Roesler, published by Sciendo.This study aimed to analyze the effect of aquatic plyometric training (APT) on jump performance in volleyball players. Twelve female athletes (16.6 ± 0.9 years) were assessed through the following jump tests: spike height (SH), squat jump (SJ), countermovement jump (CMJ) and CMJ with an arm swing (CMJA). Jump height in each test and the eccentric utilization ratio (EUR) were the outcome measures. APT consisted of sets of drop jumps for 6 weeks (2 sessions/week) at a water depth of 0.75 m. Tests were performed at the beginning of a five-week pre-season period, before and after APT, and four weeks later for the follow-up. Repeated measures ANOVAs were used to analyze data and Hedges' g to estimate effect size (ES). Performance of all jumps did not change from baseline to Pre-APT. Performance improved in SH (p < 0.001, ES: 1.09), the SJ (p = 0.045, ES: 0.76) and the CMJA (p < 0.001, ES: 0.78) after APT when compared to Pre-APT. No changes were observed after the follow-up period. In conclusion, including six weeks of APT in the training routine of youth volleyball players improved performance of a sport-specific task (SH), the SJ and CMJA, with gains preserved after a four-week follow-up.